Green human resource management: A framework for sustainable organizational development in an emerging economy. Issue 5 (6th November 2017) - Mishra, Pavitra
Abstract : Purpose: The purpose of this study is to explore the status and challenges of green human resource management practices in India, an under-researched area. Further, it proposes a theoretical framework to fill the identified gaps and build a sustainable organization. Design/methodology/approach: Multimethod approach was used. The research was conducted in two phases. Archival research was conducted in the first phase, and a case study technique was employed in the second phase. In the first phase, an extensive literature review was carried out to gather insights on prevalent green human resource activities and their link with sustainable organizational development. In the second phase, data were collected from the manufacturing organizations to analyze the status of the activities identified in the first phase. Findings: This study highlights status of green human resource practices such as environmental training, green recruitment, performance appraisal, employee involvement and compensation. The findings suggest that there is further scope to utilize the full potential of GHRM practices for encouraging pro-environmental behavior in the organizations. Analyses of data also reveal that top-management support and mutual learning among departments are crucial to facilitate green behaviors among employees. Research limitations/implications: This study provides a comprehensive literature review of green-human resource management practices. It suggests an interdisciplinary framework for building holistic sustainable organizations by integrating learnings from green human resource management, green supply-chain management, competitive advantage strategy and green corporate social responsibility. It highlights gaps in the system and provides insights to managers and policy makers on building holistic sustainable organizations. Originality/value: This study fulfills the need to explore green human resource management in emerging economies like India. Studies like these are more important in developing countries, which have alarming environmental concerns and poorly implemented government regulations.